2009
DOI: 10.1111/j.1745-4549.2008.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carrageenan and Oat Flour on Storage Characteristics of Fried Mutton Kofta

Abstract: Low‐fat high‐fiber mutton kofta containing minced meat and optimized quantities of refined wheat flour (8.5%), oat flour (8.0%) and carrageenan (0.5%) was prepared. The product with wheat flour (9.0%) and fat (8.0%) and without oat flour and carrageenan was treated as control. The product was deep fat fried, packed under air or nitrogen and stored at 4 ± 2C. Inclusion of oat flour and carrageenan resulted in substantially lower contents of fat and higher moisture content compared with control. The carrageenan‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
6
23
1
3
Order By: Relevance
“…This was in agreement with the findings of Reddy and Rao (1997), Nag et al (1998), Singh and Verma (2000), Chidanandaiah et al (2009), Reddy et al (2009, Modi et al (2009), Kumar and Tanwar (2010), Sudheer et al (2010) and Bhat et al (2010) who also found a similar increase in TBARS values upon storage of different meat products.…”
Section: Free Fatty Acids (% Oleic Acid)supporting
confidence: 92%
See 1 more Smart Citation
“…This was in agreement with the findings of Reddy and Rao (1997), Nag et al (1998), Singh and Verma (2000), Chidanandaiah et al (2009), Reddy et al (2009, Modi et al (2009), Kumar and Tanwar (2010), Sudheer et al (2010) and Bhat et al (2010) who also found a similar increase in TBARS values upon storage of different meat products.…”
Section: Free Fatty Acids (% Oleic Acid)supporting
confidence: 92%
“…The results of the study were in agreement with the findings of Awonrin (1993), Reddy and Rao (2000), Kilinc (2009), Reddy et al (2009 and Bhat et al (2010) who also reported a reduction in overall acceptability scores in chicken loaves, chicken sausage, anchovy patties and chevon Harrisa upon storage at refrigerated temperature. Furthermore, a gradual increase in FFA and TBA values explains the descending trend in the rating of sensory quality of the product during storage, and this has been reported by many researchers (Sen and Karim 2003;Andres et al 2006;Modi et al 2009). …”
Section: Sensory Parameterssupporting
confidence: 59%
“…Similar results were reported by Conca and Yang (1993), Kester and Fennema (1986), Krochta et al (1994) and Earle and McKee (1985) and Chidanandiah et al (2009) (Brewer et al 1992) that led to lipid oxidation. Dushyanthan et al (2000), Kumar and Sharma (2004), Chidanandiah et al (2009), Modi et al (2009, Kumar and Tanwar (2010), Sudheer et al (2010) and Bhat et al (2010) who also found a similar increase in TBARS values upon storage of different meat products.…”
Section: Phmentioning
confidence: 82%
“…The total trans fatty acid content was lower and the ratio of total unsaturated fatty acids to total saturated fatty acids was higher in the meatballs with added rye bran. There are reports (Modi et al 2009;Prasad et al 2011) on the use of carrageenan, oat and casein in meat products as fat replacers. Apart from reducing fat content, fibers also have numerous other health benefits like maintaining bowel integrity, antioxidative, antiobesity, hypocholesterolemic, antidiabetic, anticancerous, cardiovascular disease etc.…”
Section: Meat Incorporated Foodmentioning
confidence: 99%